Using stable distribution laws during evaluation of signal processing efficiency in optoelectronic systems - Стрелкова, Татьяна Александровна (Eastern-European Journal of Enterprise Technologies, 2015)
The changes in the statistical properties of the output signals of the optoelectronic systems with limited dynamic range when forming spatial-temporal distribution of optical radiation in the photodetector plane were analyzed. It is shown that selecting statistical models based on the central or generalized limit theorems requires considering the system operation conditions and spatial-energy characteristics of signals. Studies of the asymptotic behavior of tails of the distribution densities of the output signals have shown the possibility of using stable distribution laws for describing the signals in the optoelectronic systems. ustainable distribution laws for describing the signals in optoelectronic systems. Comparative analysis of the system detection errors, depending on the selected statistical model of output signals has shown that using stable laws is essential in evaluating the signal processing efficiency. Improving processing algorithms in optoelectronic systems taking into account a statistical model of the output signals based on stable laws allows to avoid detection errors.